BIODEGRADABLE POLYMERS: ADVANCING CHEMISTRY FOR A SUSTAINABLE FUTURE (The Research of Medical Science Review, 2025)
A potential remedy for the worldwide problem of plastic pollution and environmental deterioration is biodegradable polymers. Because they break down into non-toxic byproducts in the environment, these polymers—which come from both natural and manmade sources—offer a sustainable substitute for traditional plastics. The chemistry, production, and various uses of biodegradable polymers are examined in this overview, with a focus on how they contribute to sustainability. Important components including polylactic acid (PLA), polyhydroxyalkanoates (PHA), and polysaccharides are emphasized, along with cutting-edge green manufacturing techniques that reduce their negative effects on the environment. These materials' versatility and potential are demonstrated by their applications in biomedical sciences, packaging, agriculture, and environmental remediation. However, issues including scalability, mechanical performance, and production costs continue to be obstacles to broad adoption. A thorough overview of the field is provided in this review with the goal of stimulating more research and innovation in biodegradable polymer technology. This review also explores degradation mechanisms, life cycle analysis, and the environmental impact of biodegradable polymers, highlighting their advantages over conventional plastics. Developments in polymer chemistry, nanotechnology integration, and circular economy strategies hold promise for overcoming current limitations. Biodegradable polymers can play a paramount role in achieving a sustainable future by fostering interdisciplinary collaboration and policy support.